2015
DOI: 10.1371/journal.pone.0135347
|View full text |Cite
|
Sign up to set email alerts
|

Altered Fronto-Temporal Functional Connectivity in Individuals at Ultra-High-Risk of Developing Psychosis

Abstract: BackgroundThe superior temporal gyrus (STG) is one of the key regions implicated in psychosis, given that abnormalities in this region are associated with an increased risk of conversion from an at-risk mental state to psychosis. However, inconsistent results regarding the functional connectivity strength of the STG have been reported, and the regional heterogeneous characteristics of the STG should be considered.MethodsTo investigate the distinctive functional connection of each subregion in the STG, we parce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 60 publications
6
21
0
Order By: Relevance
“…Findings from a large number of studies converge on the superior and middle temporal cortex as critical loci of anatomical and functional pathology in schizophrenia (51) and, to a lesser extent, in the CHR period (52). Volumetric reductions of the STG(53) and morphological abnormalities of the planum temporale(54) have long been observed in different phases of the illness, and these same temporal regions have been implicated in the genesis of psychotic symptoms(55).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from a large number of studies converge on the superior and middle temporal cortex as critical loci of anatomical and functional pathology in schizophrenia (51) and, to a lesser extent, in the CHR period (52). Volumetric reductions of the STG(53) and morphological abnormalities of the planum temporale(54) have long been observed in different phases of the illness, and these same temporal regions have been implicated in the genesis of psychotic symptoms(55).…”
Section: Discussionmentioning
confidence: 99%
“…Among model-based approaches, the most widely used is the region of interest (ROI)-based method ( Biswal et al, 1995 ), which measures functional connectivity (correlation or coherence) among different ROIs or between a specified “seed” ROI and all other voxels in brain. Most previous IN studies of CHR individuals employed an ROI-based method seeded by thalamus ( Anticevic et al, 2015 ), superior temporal gyrus ( Yoon et al, 2015 ), posterior cingulate cortex ( Shim et al, 2010 ), medial prefrontal cortex and anterior insula ( Wotruba et al, 2014 ), Broca's area ( Jung et al, 2012 ), or cerebellum ( Wang et al, 2016 ). These studies computed correlations between the mean time series in a specific ROI and the time series of other voxels in brain.…”
Section: Introductionmentioning
confidence: 99%
“…These studies computed correlations between the mean time series in a specific ROI and the time series of other voxels in brain. The identified IN abnormalities of CHR individuals were primarily located in the frontal lobes ( Anticevic et al, 2015 , Jung et al, 2012 , Wang et al, 2016 , Wotruba et al, 2014 , Yoon et al, 2015 ), temporal lobes ( Yoon et al, 2015 ), thalamus ( Anticevic et al, 2015 ), sensory motor cortex ( Anticevic et al, 2015 ) and Heschl's gyrus ( Anticevic et al, 2015 ), some of which also showed an intermediate degree of abnormality in the CHR syndrome compared to first episode psychosis ( Jung et al, 2012 , Yoon et al, 2015 ). One limitation of such studies is that results depend on a somewhat arbitrary definition of a specific ROI, including delineation of its shape, extent, and precise location ( Du et al, 2012 , Liu, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In total, 14 components (Figure ) were identified as RSNs from group melodic output that included DMN; anterior DMN (ADMN); posterior DMN (PDMN); right fronto‐parietal network (RFPN); left fronto‐parietal network (LFPN); sensorimotor network (SMN); medial visual network (MVN); lateral visual network (LVN); task positive network (TPN); salience network (SN); auditory network (AN); fronto‐temporal network (FTN); basal ganglia network (BGN); and emotion network (EN) …”
Section: Resultsmentioning
confidence: 99%